Food fraud vulnerability assessment in the edible vegetable oil supply chain: A perspective of Chinese enterprises. (August 2022) - Yang, Zhaohui; Zhou, Quan; Wu, Weiliang; Zhang, Duo; Mo, Lifen; Liu, Jiali; Yang, Xingfen
Abstract: The adulteration of edible vegetable oil is simple, but the detection is difficult, so it is a common target for fraudsters. To gain insight into the fraud vulnerability of the edible vegetable oil supply chain and then take more targeted measures to prevent and mitigate food fraud, we assessed the perceived fraud vulnerability of Chinese enterprises using the SSAFE food fraud vulnerability assessment (FFVA) tool and further applied multiple correspondence analysis (MCA) and nonparametric tests (Mann–Whitney U test & Kruskal–Wallis test) to compare the differences in fraud vulnerability between tier groups. Food fraud vulnerability in the FFVA questionnaire consists of three key elements: opportunities, motivations, and control measures. The results show that (1) Fraud factors related to opportunities in the Chinese edible vegetable oil supply chain have an overall medium-high vulnerability, while those related to motivations and control measures have medium and low vulnerability, respectively. (2) Producers have significantly higher perceived fraud vulnerability in terms of opportunities and motivations than retailers. (3) In the comparison between companies and workshops of producers, the perceived fraud vulnerability was significantly higher for workshops in terms of motivations and control measures and higher for companies in terms of opportunities, indicating that workshops are more vulnerable to committing fraud driven by economics and business culture and that they lack adequate measures to control fraud, in addition to the perception by companies that they are more likely to be victims of fraud. (4) The perceived vulnerability to fraud varies by the scale of enterprises. Highlights: SSAFE FFVA tool was used to assess the fraud vulnerability of the Chinese edible oil supply chain. Fraud enablers and drivers are the crucial causes of edible vegetable oil fraud. Producers are more vulnerable to food fraud than retailers. Workshops are more likely to be driven by economic and business culture to commit fraud than companies. The perceived vulnerability to fraud varies by the scale of enterprises.